PANDANGAN FATIMA MERNISSI TENTANG KEPEMIMPINAN PEREMPUAN DI WILAYAH PUBLIK PERSPEKTIF TEORI FEMINISME EKSISTENSIALIS - Rahmatunnur, Sari; Aramina, Aramina; Ch, Mufidah (EGALITA, 2023)
This study explores  Fatima Menissi's perspective on the position and leadership of women in Islam based on existensialist feminism theory. A descriptive-qualitative approach draws on the finding from the literature Study (library research). This study uses data collection techniques based on the documentary method. The result suggest that Fatimah argues about the hadith narrated by Abu Bakrah was used to corner women in political activities. This hadith cannot be used as a reference to reject women's leadership in the public sphere. According to existentialist feminist theory, women have their own freedom and autonomy. This theory is  accordance with Fatima's opinion that women have the right to fight for their rights and freedom to make decisions in marriage, education, and employment. As long as women cannot be separated from their nature as a woman and wife. This is based on that every human being has the right to herself. Therefore, women have the right to be themselves without any pressure and become second class society. In occupying a leadership position is not based on gender (sex).